أثر تكنولوجيا المعلومات والاتصالات على النمو الاقتصادي في ليبيا: دراسة قياسية - هارون، عمران شعبان الهادي (المركز الجامعي بلحاج بوشعيب عين تموشنت - معهد العلوم الاقتصادية، التسيير والعلوم التجارية, 2023)
هدفت الدراسة الحالية إلى تقدير أثر تكنولوجيا المعلومات والاتصالات على النمو الاقتصادي في ليبيا، تم رفض ARDL خلال الفترة (1990- 2021). وعبر استخدام نموذج الانحدار الذاتي لفترات الإبطاء الموزعة فرض العدم القائل بعدم وجود علاقة تكامل مشترك بين متغيرات الدراسة، ومن ثم قبول الفرض البديل القائل بوجود إلى إمكانية تصحيح الأخطاء ECM علاقة تكامل مشترك بين هذه المتغيرات. وتشير نتائج نموذج تصحيح الخطأ قصيرة الأجل للعودة إلى الوضع التوازني طويل الأجل. ونظرا لأن حد تصحيح الخطأ معنوي عند مستوى معنوية 5%، كما أنه ظهر بإشارة سالبة، مما يؤكد وجود علاقة توازنية في الأجل الطويل، حيث بلغت قيمة حد تصحيح الخطأ 5.2، وبهذا فإن أي صدمة قصيرة الأجل سوف يتم تصحيحها خلال 0.2 سنة تقريبا. The current study's goal is to find out how information and communication technology will affect Libya's economic growth over the coming years (1990-2021). The model demonstrated that the value of F-statistic (56.3) for Model (3) is greater than the upper limit at a significant level of 5%, which confirms the rejection of the null hypothesis that there is no cointegration relationship between the variables. This model used the ARDL autoregressive distributed delay model. Accept the alternative theory that these variables are related by cointegration after conducting the investigation. The study, followed by acceptance of the alternative hypothesis that these variables are related by cointegration. Given that the error correction limit is significant at a significant level of 5% and it appeared with a negative sign, which confirms the existence of an equilibrium relationship in the long term, any short-term shock will be corrected in about 0.2 years, according to the results of the ECM error correction model.
Keywords: تكنولوجيا المعلومات -- التنمية الاقتصادية -- الاقتصاد الوطني -- ليبيا